Pengaruh Beberapa Pupuk Hayati terhadap Pertumbuhan Stek Batang Tin (Ficus carica L) - Muhammad Nizar Hanafiah Nasution; Indah Putri Agustina; Yusriani Nasution; Dina Rahmi Solihad Nasution; Yusnita Wahyuni Silitonga (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
The use of tin (Ficus carica L.) in Indonesia is still very limited and is generally only used as bonsai saplings. Tin plants can be propagated vegetative, namely the cutting technique. Selection of appropriate biological fertilizers is one of the strategies for the success of cuttings. This study aims to analyze the effect of various biological fertilizers on stem cuttings of tin plant. This research was conducted in July-October 2022, located at CV. Martabe Prima Lestari, Lubuk Raya Village, Padangsidimpuan Hutaimbaru District. The study was arranged by using Randomized Block Design (RBD), consisting of 4 treatments: P0 (control, without biological fertilizers), P1 (Trichoderma sp. 15 grams), P2 (promoles 12.15 grams) and P3 (15 grams mycorrhiza). and 6 replicates. The data obtained were analyzed by ANOVA and if there were differences, it would be continued with Duncan Multiple Range Test (DMRT). Results: Promol 12 and Micoriza, showed no significant difference in the percentage of live cuttings. Observation of time of bud break showed that the biological fertilizer treatment had no significant effect. Number of shoots showed that biological fertilizers had no significant effect on number of shoots. The average number of leaves showed that at 4 WAP(P0) was not significantly different from P1, but significantly different from P2 and P3. P1 is not significantly different from P2 but significantly different from P3, P2 is not significantly different from P3. It can be concluded that the treatment of biological fertilizers has a significant effect on the number of leaves on tin plants.